How theory meets practice: An analysis of the capital structure of Spanish SMEs - Clara Cardone Riportella; Leonardo Cazorla Papis (The Journal of Entrepreneurial Finance and Business Ventures, 2006)
The article analyzes the factors determining the capital structure of the Spanish small and medium enterprises [SMEs]. The analysis is grounded on the agency theory, the signalling approach and the pecking order theory. In particular, the article provides a qualitative and quantitative analysis about the impact of company brand, the ownership and control structure, and the relationship between the SMEs and their own financial policy. This analysis is based on defining the expected relationships that one might consider between the referred variables and the total debt ratio. In this regard, the analysis will be conducted by means of considering a survey of 410 Spanish SMEs where an ANOVA test will be applied. Then, a hierarchical regression model will allow comparison of the hypotheses made.
Keywords: 650